Al-Cu Composite’s Springback in Micro Deep Drawing - Julian Widiatmoko; Fanghui Jia; Zhengyi Jiang (Journal of Engineering and Technological Sciences, 2023)
With the recent technological trend of miniaturization in manufacturing industries, the rise of micro forming operations such as micro deep drawing (MDD) is inevitable. On the other hand, the need of more advanced materials is essential to accommodate various applications. However, a major problem are size effects that make micro scale operations challenging. One of the most important behaviors affected by size effects is the springback phenomenon, which is the tendency of a deformed material to go back to its original shape. Springback can affect dimensional accuracy, which is very important in micro products. Thus, this paper investigated the springback behavior of Al-Cu composite in MDD operations. Micro cups were fabricated from blank sheet specimens using an MDD apparatus with variation of annealing holding time. The springback values were measured and compared to each other. The results showed that different grain sizes lead to variation in the amount of springback. However, unlike in single-element materials, the amount of springback in Al-Cu composite is not only related to the thickness to grain size (t/d) ratio. Another factor, i.e., the existence of an interfacial region between layers, alters the mechanical behavior of the composite.